ClassDojo Impact on Improving Students Ability in Understanding English and Writing EFL with Platform 5.0 - Wijayanto, Pikir Wisnu; Aisah, Siti; Prabowo, Jumbuh (Jurnal Pendidikan Indonesia, 2025)
In English as a foreign language (EFL) learning, the use of technology in the teaching and learning process is increasingly gaining attention but has minimal implementation. ClassDojo has emerged as a promising tool in Platform 5.0 to improve communication between teachers and students. This is urgent to be studied because of the differences in opinion between the theory and the findings of previous researchers. This study aims to analyze the effectiveness of ClassDojo in improving EFL students' writing performance and understanding their perceptions of the use of this technology. The research method used was a quasi-experimental with a pre-test and post-test design, involving 325 students from 10 junior high schools in Bandung as samples. Data were collected through direct observation techniques, tests, and interviews. Data analysis was carried out by comparing the results of the pre-test and post-test between the experimental group using ClassDojo and the control group using SPSS version 29. The results showed a significant increase in the writing ability of students who received feedback through ClassDojo, including aspects of task achievement, coherence, lexical resources, and grammatical accuracy. These findings indicate that the use of ClassDojo is not only effective in improving academic outcomes but also increasing student engagement in EFL language and writing learning. The implications of this study encourage educational stakeholders to adopt technology-based pedagogical innovations in the learning process. Suggestions, apply more holistically about students' learning experiences using technology in EFL contexts.